2003
DOI: 10.3349/ymj.2003.44.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Stroke in the Brain and Spinal Cord Following an Induced Hypotension

Abstract: A 49-year-old woman presented with stupor and paraplegia following an induced hypotension. The temporal relationship to the induced hypotension and the absence of a clear embolic source on diagnostic tests support a causal association between the hypotensive episode and the ischemic infarct. However, despite the association, a cause-and-effect relationship could not be automatically inferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The thoracic region has the largest spacing between radicular arteries in comparison to other spinal segments 10. A watershed zone of increased ischemic vulnerability is located at the interface of the anterior and posterior spinal artery territories, described by many authorities to be at the level of T4 46,10. The extent of this patient’s lesion suggests a particularly large area of ischemic vulnerability in the distribution of the anterior spinal artery.…”
Section: Discussionmentioning
confidence: 99%
“…The thoracic region has the largest spacing between radicular arteries in comparison to other spinal segments 10. A watershed zone of increased ischemic vulnerability is located at the interface of the anterior and posterior spinal artery territories, described by many authorities to be at the level of T4 46,10. The extent of this patient’s lesion suggests a particularly large area of ischemic vulnerability in the distribution of the anterior spinal artery.…”
Section: Discussionmentioning
confidence: 99%
“…However, deliberate hypotension has a potential risk of multiple complications. Even within “a safe range of hypotension,” brain damage, stroke, and death may still occur [9]. It is reported in the early 1950s that mortality associated with deliberate hypotension is about 0.22% to 0.34%, and nonfatal complications mainly referred to cerebral, coronary, and renal circulations occur 908 times (about 2.6% to 3.3%) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Acknowledging that excessive bleeding may impair surgery, extreme hypotension may in turn risk organ hypoperfusion and subsequent ischemic injury . Since the inception of hypotensive anesthesia, a number of authors have reported neurological injury attributable to inadequate cerebral perfusion .…”
Section: Introductionmentioning
confidence: 99%
“…Acknowledging that excessive bleeding may impair surgery, extreme hypotension may in turn risk organ hypoperfusion and subsequent ischemic injury . Since the inception of hypotensive anesthesia, a number of authors have reported neurological injury attributable to inadequate cerebral perfusion . Conversely, current literature also reports no short‐ and/or long‐term adverse effects on cerebral, hepatic, and renal function with this technique …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation